Basic Dimensions of Early Reading Skills of Elementary School Students in Bandung - Damaianti, Vismaia Sabariah; Rahma, Rosita; Astini, Meilani Puji (Universitas Negeri Malang, 2020)
This study is motivated by the need for a descriptive and analytical research related to the basic dimensions of early reading skills of elementary school students to determine the level of students’ reading skills, including their difficulties in learning to read. This study aims to get a picture of the early reading skills of elementary school students in Bandung. The results of this study can be used as a guide for education practitioners, policy makers, and related institutions. Through a descriptive and analytical method, the findings are (1) 98percent of students are able to identify letters in words, to analyze words, to identify the direction of letters, and to arrange letters into words. (2) 96percent of students are able to strip words into syllables, to sort syllables in words, to identify words with the same forms, to identify words with the same meanings, to replace words with logical words, to insert words in incomplete sentences, and to identify abstract words. (3) The students seem to have difficulties in identifying similar consonant sounds, in identifying similarities in vowel and schwa sounds, in identifying sounds that are similar in sentences, and in identifying reversed sounds. Only 57percent of students do not encounter obstacles. (4) 90percent of students are capable of making sentences from random words, making sentences from words that are not sequential, correcting sentences that have wrong words, identifying simple sentences in paragraphs, and understanding simple sentences. (5) 70percent of students have the ability to understand shapes, sizes, locations, and colors. This study has implications for the need for an integrated remedial program that can be used by both teachers and parents, especially for students who have difficulties with sound identification abilities.